Katalog Digital Bangunan Komersial Sebagai Media Promosi Berbasis Augmented Reality - Dijaya, Rohman; Hibatullah Putra, Dimas Radito; Eviyanti, Ade; Taurusta, Cindy (Journal of Technology and System Information, 2024)
Many building promotion techniques use building miniatures, but this media is less interactive. Augmented reality is a technology that allows interaction between the real and virtual worlds. To assist promotional activities, it is necessary to develop commercial building promotional media using the application " Digital Catalog of Commercial Buildings Based on Augmented Reality as Promotional Media". Building objects are made in three dimensions and visualized through augmented reality technology. The purpose of developing this application is as a medium or tool to facilitate the communication process with customers. Application development uses the Multimedia Development Life Cycle method and has been successfully operated on several devices with the Android operating system. From the results of black-box and feasibility testing, the application gets good results and has a score of 913 out of 1000 or 91.3% percentage of eligibility.